Dyskurs feministyczny i kategoria gendera współczesna literatura rosyjska. Zarys teoretyczny - Borodzicz-Chiszko, Monika (Acta Polono-Ruthenica, 2010)
The article is devoted to the problem of feminism and gender in Russia and their influence on the development of contemporary womens prose. The article deals with the most important features of Russian feminism taking into account the differences in relation to the movement in Western Europe. The author pays special attention to the influence of orthodox religion on the development of feminism in Russia as well as to the specific view of the role of woman and man in the society resulting from Russian culture. Religious and cultural impact over the specific character of Russian feminism is connected with the fact that in Russia a greater emphasis is placed on gender and not on sex. Therefore, the author believes that feminism in Russia has stimulated creativity of women in different fields of art and especially in literature.